Experience of using an infrared camera in the study of astronomical objects - Solodovnik А.А.; Useinov, B.M.; Kassenov, T.B.; Zhuravlev, P.L.; Solodovnik, N.P. (Recent Contributions to Physics, 2026)
Based on the analysis of images of comet C/2023 A3 Tsuchinshan-ATLAS, obtained in both visible light and near-infrared range (wavelength over 850 nm) using CANON EOS 2000D and CANON EOS 1000DI (infrared) cameras, the influence of the observation spectral range on image contrast is studied. The image quality criterion is its contrast. Contrast coefficient calculations were performed using the standard ImageJ program used for image processing and analysis in various scientific applications. Several approaches to determining comet image contrast were used. Comparison of the obtained results did not reveal significant advantages of shooting in the mentioned spectral ranges. However, the analysis of noctilucent cloud images obtained using the same methodology revealed a significant advantage of infrared imaging, which sharply increases image contrast. A detailed analysis of shooting conditions suggested that the reduced effectiveness of infrared imaging is due to the transition from light scattering conditions of the daytime sky to twilight, and then to night conditions. A rationale is proposed for further studying methods of improving imaging efficiency when transitioning from the visible spectrum range to the near-infrared spectrum range.